1999
DOI: 10.1016/s0735-1097(98)00681-0
|View full text |Cite
|
Sign up to set email alerts
|

Impaired endothelial function following a meal rich in used cooking fat

Abstract: Ingestion of a meal rich in fat previously used for deep frying in a commercial fast food restaurant resulted in impaired arterial endothelial function. These findings suggest that intake of degradation products of heated fat contribute to endothelial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(127 citation statements)
references
References 26 publications
6
118
1
2
Order By: Relevance
“…NO production from healthy endothelial cells has an antiatherogenic effect by inhibiting cellular adhesion, migration, and proliferation responses involved in early lesion formation. 5,6 Transient reductions in endothelial function have previously been reported after a high fat meal, 25 in drug-induced hyperhomocysteinemia, 26 and in the inflammatory response to vaccination 27 and might contribute to the pathogenesis of atherosclerosis. Studies in the cynomolgus monkey have shown that chronic social conflict increases the rate of endothelial cell damage 12 and reduces NO bioavailability in the coronary arteries.…”
Section: Discussionmentioning
confidence: 96%
“…NO production from healthy endothelial cells has an antiatherogenic effect by inhibiting cellular adhesion, migration, and proliferation responses involved in early lesion formation. 5,6 Transient reductions in endothelial function have previously been reported after a high fat meal, 25 in drug-induced hyperhomocysteinemia, 26 and in the inflammatory response to vaccination 27 and might contribute to the pathogenesis of atherosclerosis. Studies in the cynomolgus monkey have shown that chronic social conflict increases the rate of endothelial cell damage 12 and reduces NO bioavailability in the coronary arteries.…”
Section: Discussionmentioning
confidence: 96%
“…Frying can greatly alter a fish meal's nutrient composition, increasing contents of n-6 fatty acids, trans-fatty acids, and oxidation products, particularly when oils are used repeatedly for frying. [35][36] Adjustment for baseline coronary heart disease, left ventricular systolic function, blood pressure, treated hypertension, and C-reactive protein levels attenuated the higher AF risk seen with fried fish/fish sandwich intake, which suggests that these factors may in part confound or mediate the association. Further investigation is necessary to confirm these observations, determine if they are specific for certain kinds of fish or frying oils, and examine potential mechanisms and alternative explanations.…”
Section: Discussionmentioning
confidence: 99%
“…This might, at least in part, be due to important distinctions between various antioxidants, i.e., their ability to quench free radical activity, and their localization within the vascular wall. However, mechanistic study of chronic uric acid elevation may prove more of a challenge, and the current study design appears to be a valid approach because acute elevation of established major cardiovascular risk factors causes impaired endothelial function in healthy individuals, i.e., after ingestion of a meal rich in saturic acid fats (41) or after raising circulating homocysteine concentrations by oral methionine administration (42). Assessment of endothelial function as a risk marker appears valid because of correlations between short-and long-term effects of interventions that are known to be effective in reducing cardiovascular risk, i.e., blood pressure lowering and statin therapy (43,44).…”
Section: Discussionmentioning
confidence: 99%